PILKADA SEBAGAI SARANA PEMBERDAYAAN POLITIK YANG BERMARTABAT DAN DEMOKRATIS (Suatu Tinjauan Etika dan Politik Hukum) - Firdaus Syam (Perspektif, 2007)
In context election of regional leader, [at] its it [him] political ethics and norm have important role in grow the way of regional leader candidate someone approach. Integrity ability and moralitas [do] not only measured from its efficacy of meraup as much as possible elector voice, much more important from that is how its strength of him to followed election process it better this cover; understanding of order procedure, standard, election mechanism, and do not less important develop; build cultural communications as sensitivity form or its of.